Reducing pesticides without organic certification?: Potentials and limits of an intermediate form of agricultural production - Koch, Marcus; Tosun, Jale; Kellermann, Laura; Marek, Charlene; Kiefer, Markus; Thiv, Mike (Cogent food & agriculture, 2023)
A growing number of farmers’ cooperatives cultivate crops without chemical pesticides, but also without organic certification. How does this intermediate form of agriculture between conventional and organic production function? What are the outcomes of this production form on cropland biodiversity? How does this model contribute to the transition toward more sustainable forms of agriculture? We address these research questions using the original data collected in the AgroBioDiv project from the farmers’ cooperative “KraichgauKorn” based in the German Federal State of Baden-Württemberg. This cooperative is a collection of conventional farmers, who refrain from pesticide use during the growing seasons for KraichgauKorn cereal grains. Our study finds higher levels of weed species biodiversity on KGK cereal fields compared to conventional fields, but lower levels of biodiversity than on organic fields. In addition, more endangered wild species monitored by the State of Baden-Württemberg were found on KGK fields than conventional fields, with organic fields exhibiting the highest presence of endangered flora. We conclude that such kinds of enterprises may indeed contribute substantially to a successful transformation towards sustainable agricultural systems.